Rhinitis in Children: Current Aspects of Diagnosis and Treatment - E. A. Vishneva; L. S. Namazova-Baranova; L. R. Selimzyanova; A. A. Alekseeva (Union of pediatricians of Russia, 2016)
The article is devoted to one of the most urgent problems of pediatrics - rhinitis in children. The difficulty of nasal breathing, being one of the most frequent complaints to pediatricians, can be caused by a banal respiratory infection, as well as be one of the systemic pathology's symptoms. The economic burden of rhinitis is great for any health budget, the total direct and indirect costs are huge. The article shows the main phenotypic characteristics of rhinitis depending on the etiological factor; gives the modern principles of differential diagnostic search; points studies, use of which is not recommended in routine practice. The authors reflect the key components of a complex therapy and discuss in detail the tactics and possible pharmacological treatment strategies.